Relationship between substance abuse knowledge, competency and self-efficacy towards success of methadone maintenance therapy among counselors - Mariapah, Sinthumathi; Ahmad, Jamaluddin; Wan Jaafar, Wan Marzuki (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Methadone Maintenance Therapy (MMT) is an effective treatment to treat opiate abusers and its effectiveness is well documented especially among opiate users. Thus, this study reviews about the relationship between substance abuse knowledge, competency and self-efficacy towards success of Methadone Maintenance Therapy among counsellors. The effectiveness or the success of the MMT does not depend only on the client outcome but the outcomes were associated with the involvement of counsellors as service provider. Respondents will need to complete a set of questionnaire encompasses of three instruments about knowledge, competency and self-efficacy. This research hopefully contributes to the understanding of the importance of these variables among counsellors towards the success of MMT.